The Decision Problem for Decision Problems - Gurevich, Yuri (Algebra and Logic, 1969)
Consider the collection D of first-order formulas α such that the first-order theory with axiom α is decidable. It is proven that D is neither r.e. nor co-r.e. (The second part has been known earlier.)